Students’ Motivation in Learning English After the Practice of Teacher-in-Role - Latifah Syuhada; Sitti Fatimah (Universitas Negeri Padang, 2021)
Teacher's strategy in teaching English determines students’ motivation in learning English.Students who have low motivation in learning English have been identified as having low competence in English. This study intended to figure out how is Students’ motivation in learning English after the practice of Teacher-in-Role(TiR).Teacher-in-Role is one of the elements of Drama on process and as the starting point for this research to enhance students’ motivation in learning English. Students areencouragedto express their thoughts and feelings while evaluating their own attitudes and skills as they consider the feelings and beliefs of others. The study employed descriptive qualitative and quantitative design. There were 32 students that have observed and involved in this research. The data were collected by using instruments, namely: questionnaire sheet and focus group discussion. Based on the data analysis, it was found that , students’ motivation after the practice of Teacher-in-Role has shown a good result. It concluded from three indicators of motivation that have been observed. Those are positive manner, desire to integrated and more persistence in learning English. The percentage of each aspects is quite higher. Students were exited, fun, and enjoy the learning process while they were practicing Teacher-in-Role, albeit some students uttered that they were worried and afraid making mistakes while talking English because of the lack of vocabularies.